2014
DOI: 10.1038/srep04183
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism is a Risk Factor for Developing Adhesive Capsulitis of the Shoulder: A Nationwide Longitudinal Population-Based Study

Abstract: The purpose of this study was to investigate the prevalence and risk of adhesive capsulitis among hyperthyroidism patients. The data were obtained from the Longitudinal Health Insurance Database 2005 (LHID 2005) in Taiwan, using 1 million participants and a prospective population-based 7-year cohort study of survival analysis. The ambulatory-care claim records of patients diagnosed according to the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes relating to hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 24 publications
(30 reference statements)
0
31
1
2
Order By: Relevance
“…Unexpectedly, in our results, patients with thyroid disease showed a lower risk of AC than the group without thyroid disease (Table ). Huang et al reported a population study in Taiwan and showed hyperthyroidism to be a risk factor for developing AC. However, their study specifically aimed at hyperthyroidism patients and did not include other thyroid diseases such as hypothyroidism, thyroid cancer or nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, in our results, patients with thyroid disease showed a lower risk of AC than the group without thyroid disease (Table ). Huang et al reported a population study in Taiwan and showed hyperthyroidism to be a risk factor for developing AC. However, their study specifically aimed at hyperthyroidism patients and did not include other thyroid diseases such as hypothyroidism, thyroid cancer or nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have revealed that comorbidities with thyroid disease, carotid artery disease (CAD), diabetes mellitus (DM), hyperlipidemia and stroke may lead to the development of AC. Indeed, two previous longitudinal population‐based follow‐up studies reported that hyperthyroidism and DM are independent risk factors for the development of AC …”
Section: Introductionmentioning
confidence: 99%
“…1,[6][7][8] These observations suggest that the etiology of frozen shoulder is fundamentally related to inflammatory reactions. However, past studies have revealed comorbidities such as diabetes mellitus, Dupuytren's contracture, hypothyroidism, hyperthyroidism, and Parkinson's disease in frozen shoulder, [9][10][11] indicating that hormonal and genetic factors are potentially involved in its development. 1,2 These observations suggest that understanding the etiology at the molecular level is essential to establish better therapeutic interventions and prophylaxis for frozen shoulder.…”
mentioning
confidence: 99%
“…3-5% of the population is diagnosed with "frozen shoulder syndrome", usually people with diabetes and hyperthyroidism aged 40-59 [31,46]. the pains may appear suddenly and progress gradually.…”
Section: Epidemiologymentioning
confidence: 99%